Phytic acid-Ti3C2 MXene composite material and preparation method thereof

By preparing phytic acid-Ti3C2 MXene composite, the problems of small layer spacing and easy expansion of Ti3C2 MXene material are solved, the specific capacity and cycle stability of the negative electrode of the potassium ion battery are improved, the diffusion and charge transport of potassium ions are optimized, and the Rate performance.

CN119153646AActive Publication Date: 2024-12-17GUANGDONG UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411157698.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2024-12-17
Estimated Expiration
2044-08-22

AI Technical Summary

Technical Problem

Ti3C2 MXene material has a small layer spacing in the anode material of potassium ion battery and is prone to volume expansion, affecting the embedding and disengagement of potassium ions, resulting in poor circulation stability and rate performance.

Method used

The preparation method of phytic acid and Ti3C2 MXene composite material is adopted. After stirring evenly, liquid nitrogen freezes and freeze-drying, increase the material layer spacing and form aerogel. Then heat treatment is carried out under an inert atmosphere to increase the layer spacing and promote phytic acid. The tight attachment to the Ti3C2 MXene material forms a phytic acid-Ti3C2 MXene composite material.

Benefits of technology

The specific capacity and cyclic stability of the negative electrode material of the potassium ion battery are significantly improved, the layered stacking and volume expansion of Ti3C2 MXene are inhibited, the diffusion channel and charge transport path of the potassium ion are optimized, and the rate performance of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153646A_ABST
    Figure CN119153646A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery electrode materials, and provides a phytic acid-Ti3C2MXene composite material and a preparation method thereof.The preparation method comprises the steps that Ti3C2MXene, phytic acid and a dissolution promoter are placed in a solvent to be evenly stirred to obtain a mixed solution, liquid nitrogen is used for freezing to obtain a solid product, the solid product is subjected to freeze drying under the vacuum condition to obtain aerogel, and the aerogel is used for preparing the Ti3C2MXene / phytic acid-Ti3C2MXene / phytic acid-Ti3C2MXene / phytic acid-Ti3C2MXene composite material. And carrying out heat treatment on the aerogel in an inert atmosphere, and cooling to room temperature to obtain the phytic acid-Ti3C2MXene composite material. In the phytic acid-Ti < 3 > C < 2 > MXene composite material prepared by the method, phytic acid is coated on the outer surface of Ti < 3 > C < 2 > MXene and is intercalated between layers of the Ti < 3 > C < 2 > MXene, so that stacking and volume expansion of the Ti < 3 > C < 2 > MXene are effectively inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery electrode materials, and more specifically, relates to a preparation method and application of a phytic acid-Ti3C2MXene composite material. Background Art

[0002] Lithium-ion batteries have been widely used in portable digital products, electric vehicles and energy storage due to their advantages such as high open circuit voltage, long cycle life, high energy density and no memory effect. However, due to the low storage capacity of lithium in nature and high price, the further development of lithium-ion batteries in electric vehicles and large-scale energy storage is limited. Metallic potassium is abundant and inexpensive in nature, making it an ideal material to replace lithium. In order to meet people's sustainable demand for high energy density potassium-ion batteries, improving the specific capacity and cycle stability of potassium-ion battery negative electrode materials has become an important research direction for potassium-ion batteries.

[0003] MXene materials have metallic conductivity and complex surface chemical properties, and are promising emerging materials in the field of energy storage materials. In particular, Ti3C2 MXene materials have many advantages for use as negative electrode materials for potassium ion batteries. They can be peeled off from top to bottom into two-dimensional layered materials and have good conductivity and high specific surface area. Secondly, Ti3C2 MXene materials have high conductivity and high specific surface area; thirdly, Ti3C2 MXene materials can obtain higher performance through doping and surface modification. However, the interlayer spacing of Ti3C2 MXene materials is small, and during the charge and discharge cycle, Ti3C2 Mxene is prone to volume expansion and form a layered stack of Ti3C2 MXene, which is not conducive to the deintercalation of potassium ions. Therefore, it is hoped that a negative electrode material for Ti3C2 MXene potassium ion batteries with further improved electrochemical performance can be developed. Summary of the invention

[0004] In order to solve the above-mentioned defects of the prior art, the object of the present invention is to provide a method for preparing a phytic acid-Ti3C2MXene composite material. The phytic acid-Ti3C2MXene composite material prepared by the preparation method has high specific capacity, rate performance and cycle stability as an electrode material for potassium ion batteries.

[0005] Another object of the present invention is to provide a phytic acid-Ti3C2 MXene composite material.

[0006] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0007] A method for preparing a phytic acid-Ti3C2 MXene composite material comprises the following steps:

[0008] S1. Ti3C2 Mxene, phytic acid and a solvent are placed in a solvent and stirred to obtain a mixed solution;

[0009] S2. freezing the mixed solution obtained in step S1 with liquid nitrogen to obtain a solid product;

[0010] S3. freeze-drying the solid product obtained in step S2 under vacuum conditions to obtain an aerogel;

[0011] S4. The aerogel obtained in step S3 is heat-treated under an inert atmosphere and then cooled to room temperature to obtain a phytic acid-Ti3C2MXene composite material;

[0012] In the step S1, the mass ratio of Ti3C2 Mxene to phytic acid is 1:1.5-5.

[0013] The present invention firstly stirs and mixes Ti3C2 MXene, phytic acid and a solvent, and then a part of the phytic acid etches the Ti3C2 MXene material, which can increase the specific surface area of ​​the material, facilitate the full contact between the electrode and the electrolyte, expose more active sites, and thus improve the specific capacity of the electrode material; the other part of the phytic acid fully enters the interlayer of the Ti3C2 MXene material, increases the interlayer spacing, prevents the Ti3C2 MXene material from stacking after multiple insertion and extraction of potassium ions, optimizes the potassium ion diffusion channel, and increases the diffusion rate of lithium ions, thereby effectively improving the material rate performance.

[0014] The material is then rapidly frozen using liquid nitrogen to obtain fluffy aerogel, which can increase the gaps between material layers and help increase the diffusion rate of potassium ions. In addition, the use of liquid nitrogen freezing can keep the Ti3C2 MXene layered structure and the phytic acid attached to the Ti3C2 MXene surface structure unchanged to the greatest extent. The material is then freeze-dried to remove moisture from the material while ensuring that the material structure remains unchanged, so that the interlayer spacing of the material remains unchanged. Sintering is then performed to promote full compounding of the material, which is beneficial for phytic acid and Ti3C2 MXene materials to be connected and tightly attached to the surface of the Ti3C2 MXene material, thereby obtaining a phytic acid-Ti3C2Mxene composite material (P@TC).

[0015] Phytic acid has abundant hydroxyl groups, which can effectively enhance the hydrogen bond interaction between P and Ti3C2 Mxene layers, ensuring that the two can be effectively combined together. The structure of phytic acid is that six phosphate groups are symmetrically connected to the cyclohexane hexol ring, each phosphate group can dissociate and provide two protons, and phytic acid has a spatially stable conformation, with one phosphate group at the carbon 2 position in the axial position and five phosphate groups at the equatorial position. This structure is easy to interact with positively charged metal ions, so the phytic acid-Ti3C2 Mxene composite material prepared by the present invention can provide more opportunities for the embedding of potassium ions, and its application in the negative electrode of potassium ion batteries can significantly improve its capacity.

[0016] Furthermore, in step S1, the mass ratio of Ti3C2 Mxene to phytic acid is 1:1.5-2.5.

[0017] Furthermore, the heat treatment in step S4 is to increase the temperature from ambient temperature to 500-600° C. at a heating rate of 1-10° C. / min and then keep the temperature.

[0018] Calcination within this temperature range is conducive to the formation of disordered carbon structure. The increase of disordered carbon structure makes the prepared phytic acid-Ti3C2 Mxene composite material have more active sites and provides more defects, which is conducive to the embedding and extraction of potassium ions, thereby improving the rate performance of the electrode material.

[0019] Furthermore, the heat treatment and heat preservation time in step S4 is 1 to 3 hours.

[0020] Furthermore, the inert atmosphere in step S4 is nitrogen and / or argon, preferably argon.

[0021] Furthermore, the solubilizing agent in step S1 is one or more of polyethylene glycol, N,N-dimethylformamide, and dimethyl sulfoxide. Preferably, the solubilizing agent is polyethylene glycol, wherein the molecular weight of polyethylene glycol is 400. The addition of the solubilizing agent is beneficial to assist the phytic acid molecules to enter the interlayer of the Ti3C2 MXene material.

[0022] Furthermore, in step S1, the mass ratio of the solubilizing agent to the phytic acid is 1:60-200.

[0023] Furthermore, the solvent in step S1 is deionized water and / or N-methylpyrrolidone.

[0024] Furthermore, the stirring time in step S1 is 1 to 3 hours.

[0025] Furthermore, the temperature of the liquid nitrogen freezing in step S2 is -160 to -200°C.

[0026] Furthermore, the liquid nitrogen freezing time in step S2 is 5 to 20 minutes.

[0027] Furthermore, the freeze-drying time in step S3 is 48 to 96 hours.

[0028] Furthermore, the freeze drying in step S3 is performed in a freeze dryer.

[0029] Furthermore, the present invention also provides an electrode, which comprises the phytic acid-Ti3C2MXene composite material prepared by the above preparation method.

[0030] Furthermore, the weight percentage of the phytic acid-Ti3C2 MXene composite material in the electrode is 65-75%.

[0031] Furthermore, the present invention also provides a method for preparing an electrode: the phytic acid-Ti3C2Mxene composite material (P@TC) obtained above is mixed with acetylene black and a binder PVDF, and N-methylpyrrolidone is added and stirred to form a uniform slurry, which is coated on a copper foil and vacuum dried to obtain an electrode sheet.

[0032] Furthermore, the present invention also provides a potassium ion battery, which comprises the electrode prepared as above.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] In the phytic acid-Ti3C2 MXene composite material prepared by the present invention, phytic acid is coated on the outer surface of Ti3C2 MXene and intercalated between the layers of Ti3C2 MXene. The synergistic effect of the two enables the prepared phytic acid-Ti3C2 MXene composite material to maintain a layered structure while increasing the interlayer spacing, broadening the diffusion of potassium ions and the path of charge transfer, effectively inhibiting the stacking and volume expansion of Ti3C2 MXene, thereby significantly improving the material rate performance and cycle stability. In addition, since phytic acid easily interacts with positively charged metal ions, it provides more active sites for the embedding of potassium ions, thereby further improving the capacity of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is the XRD spectrum of the phytic acid-Ti3C2 Mxene composite material obtained in Example 1 of the present invention.

[0036] Figure 2 a and Figure 2 b correspond to the SEM images of Ti3C2Mxene material and the phytic acid-Ti3C2Mxene composite material of Example 1 of the present invention.

[0037] Figure 3 a and Figure 3 b correspond to the TEM images of Ti3C2Mxene material and the phytic acid-Ti3C2Mxene composite material of Example 1 of the present invention.

[0038] Figure 4 The phytic acid-Ti3C2 MXene composite material of Example 1 of the present invention and the Ti3C2 MXene material used in Comparative Example 1 were used to make a button battery at 100 mAg -1 Charge and discharge cycle performance diagram under current density.

[0039] Figure 5 The phytic acid-Ti3C2 Mxene composite material of Example 1 of the present invention is made into a button battery at 1000mAg -1 Charge and discharge cycle performance diagram under current density.

[0040] Figure 6 The phytic acid-Ti3C2 MXene composite material of Example 1 of the present invention and the Ti3C2 MXene material used in Comparative Example 1 are used to make button batteries at 100-1000 mAg -1 Charge and discharge rate performance diagram under current density. DETAILED DESCRIPTION

[0041] The content of the present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present embodiment are conventional reagents, methods and equipment in the art.

[0042] The Ti3C2 Mxene material described in the present invention was purchased from Suzhou Beike Nanotechnology Co., Ltd., CAS No.: 12363-89-2.

[0043] Example 1

[0044] A method for preparing a phytic acid-Ti3C2 MXene composite material comprises the following steps:

[0045] S1. Weigh 0.2g Ti3C2 Mxene, 0.3g phytic acid and 0.005g polyethylene glycol (400) in pure water and stir for 2h;

[0046] S2. The mixed solution obtained in step S1 is frozen at -200°C using liquid nitrogen for 10 min to obtain a solid product;

[0047] S3. The solid product obtained by freezing with liquid nitrogen in step S2 was freeze-dried under vacuum conditions for 96 hours to obtain a fluffy aerogel;

[0048] S4. Grind the aerogel obtained in step S3 and heat it from 25°C to 500°C at a heating rate of 5°C / min under an inert atmosphere for 3 hours, and cool it naturally to room temperature to obtain the target product, phytic acid-Ti3C2 MXene composite material.

[0049] This embodiment also provides a method for preparing an electrode sheet: the phytic acid-Ti3C2 Mxene composite material (P@TC) obtained above is mixed with acetylene black and binder PVDF in a mass ratio of 7.0:1.5:1.5, and N-methylpyrrolidone is added for stirring to form a uniform slurry, which is coated on a copper foil and dried in a vacuum drying oven for 12 hours to obtain an electrode sheet.

[0050] Example 2

[0051] A method for preparing a phytic acid-Ti3C2 MXene composite material comprises the following steps:

[0052] S1. Weigh 0.2g Ti3C2 Mxene, 0.5g phytic acid and 0.005g polyethylene glycol (400) in pure water and stir for 2h;

[0053] S2. The mixed solution obtained in step S1 is frozen at -200°C using liquid nitrogen for 10 min to obtain a solid product;

[0054] S3. The solid product obtained by freezing with liquid nitrogen in step S2 was freeze-dried under vacuum conditions for 96 hours to obtain a fluffy aerogel;

[0055] S4. Grind the aerogel obtained in step S3 and heat it from 25°C to 500°C at a heating rate of 5°C / min under an inert atmosphere for 3 hours, and cool it naturally to room temperature to obtain the target product, phytic acid-Ti3C2 MXene composite material.

[0056] This embodiment also provides a method for preparing an electrode sheet: the phytic acid-Ti3C2 Mxene composite material (P@TC) obtained above is mixed with acetylene black and binder PVDF in a mass ratio of 7.0:1.5:1.5, and N-methylpyrrolidone is added for stirring to form a uniform slurry, which is coated on a copper foil and dried in a vacuum drying oven for 12 hours to obtain an electrode sheet.

[0057] Example 3

[0058] A method for preparing a phytic acid-Ti3C2 MXene composite material comprises the following steps:

[0059] S1. Weigh 0.2g Ti3C2 Mxene, 0.3g phytic acid and 0.005g polyethylene glycol (400) in pure water and stir for 2h;

[0060] S2. The mixed solution obtained in step S1 is frozen at -200°C using liquid nitrogen for 10 min to obtain a solid product;

[0061] S3. The solid product obtained by freezing with liquid nitrogen in step S2 was freeze-dried under vacuum conditions for 72 hours to obtain a fluffy aerogel;

[0062] S4. Grind the aerogel obtained in step S3 and heat it from 25°C to 600°C at a heating rate of 1°C / min under an inert atmosphere for 2 hours, and cool it naturally to room temperature to obtain the target product, phytic acid-Ti3C2 MXene composite material.

[0063] This embodiment also provides a method for preparing an electrode sheet: the phytic acid-Ti3C2 Mxene composite material (P@TC) obtained above is mixed with acetylene black and binder PVDF in a mass ratio of 7.5:1.25:1.25, and N-methylpyrrolidone is added for stirring to form a uniform slurry, which is coated on a copper foil and dried in a vacuum drying oven for 12 hours to obtain an electrode sheet.

[0064] Example 4

[0065] A method for preparing a phytic acid-Ti3C2 MXene composite material comprises the following steps:

[0066] S1. Weigh 0.2g Ti3C2 Mxene, 0.3g phytic acid and 0.005g polyethylene glycol (400) in pure water and stir for 2h;

[0067] S2. The mixed solution obtained in step S1 is frozen at -200°C using liquid nitrogen for 10 min to obtain a solid product;

[0068] S3. The solid product obtained by freezing with liquid nitrogen in step S2 was freeze-dried under vacuum conditions for 72 hours to obtain a fluffy aerogel;

[0069] S4. Grind the aerogel obtained in step S3, heat it from 25°C to 500°C at a heating rate of 10°C / min under an inert atmosphere for 2 hours, and cool it naturally to room temperature to obtain the target product, phytic acid-Ti3C2 MXene composite material.

[0070] This embodiment also provides a method for preparing an electrode sheet: the phytic acid-Ti3C2 Mxene composite material (P@TC) obtained above is mixed with acetylene black and binder PVDF in a mass ratio of 6.5:1.75:1.75, and N-methylpyrrolidone is added for stirring to form a uniform slurry, which is coated on a copper foil and dried in a vacuum drying oven for 12 hours to obtain an electrode sheet.

[0071] Example 5

[0072] A method for preparing a phytic acid-Ti3C2 MXene composite material comprises the following steps:

[0073] S1. Weigh 0.2g Ti3C2 Mxene, 0.3g phytic acid and 0.005g polyethylene glycol (400) in pure water and stir for 2h;

[0074] S2. The mixed solution obtained in step S1 is frozen at -200°C using liquid nitrogen for 10 min to obtain a solid product;

[0075] S3. The solid product obtained by freezing with liquid nitrogen in step S2 was freeze-dried under vacuum conditions for 96 hours to obtain a fluffy aerogel;

[0076] S4. Grind the aerogel obtained in step S3 and heat it from 25°C to 550°C at a heating rate of 5°C / min under an inert atmosphere for 1.2 h, and cool it naturally to room temperature to obtain the target product, phytic acid-Ti3C2 MXene composite material.

[0077] This embodiment also provides a method for preparing an electrode sheet: the phytic acid-Ti3C2 Mxene composite material (P@TC) obtained above is mixed with acetylene black and binder PVDF in a mass ratio of 7.0:1.5:1.5, and N-methylpyrrolidone is added for stirring to form a uniform slurry, which is coated on a copper foil and dried in a vacuum drying oven for 12 hours to obtain an electrode sheet.

[0078] Example 6

[0079] A method for preparing a phytic acid-Ti3C2 MXene composite material comprises the following steps:

[0080] S1. Weigh 0.2g Ti3C2 Mxene, 1.0g phytic acid and 0.005g polyethylene glycol (400) in pure water and stir for 2h;

[0081] S2. The mixed solution obtained in step S1 is frozen at -200°C using liquid nitrogen for 10 min to obtain a solid product;

[0082] S3. The solid product obtained by freezing with liquid nitrogen in step S2 was freeze-dried under vacuum conditions for 96 hours to obtain a fluffy aerogel;

[0083] S4. Grind the aerogel obtained in step S3 and heat it from 25°C to 550°C at a heating rate of 5°C / min under an inert atmosphere for 1.2 h, and cool it naturally to room temperature to obtain the target product, phytic acid-Ti3C2 MXene composite material.

[0084] This embodiment also provides a method for preparing an electrode sheet: the phytic acid-Ti3C2 Mxene composite material (P@TC) obtained above is mixed with acetylene black and binder PVDF in a mass ratio of 7.0:1.5:1.5, and N-methylpyrrolidone is added for stirring to form a uniform slurry, which is coated on a copper foil and dried in a vacuum drying oven for 12 hours to obtain an electrode sheet.

[0085] Comparative Example 1

[0086] This comparative example also provides a method for preparing a negative electrode sheet: Ti3C2 Mxene is mixed with acetylene black and a binder PVDF in a mass ratio of 7.0:1.5:1.5, and N-methylpyrrolidone is added for stirring to form a uniform slurry, which is coated on a copper foil and dried in a vacuum drying oven for 12 hours to obtain a negative electrode sheet.

[0087] Comparative Example 2

[0088] The difference between this comparative example and Example 1 is that the amount of phytic acid in step S1 is 0.15 g.

[0089] Comparative Example 3

[0090] A method for preparing a phytic acid-Ti3C2 MXene composite material comprises the following steps:

[0091] S1. Weigh 0.2g Ti3C2 Mxene, 0.3g phytic acid and 0.005g polyethylene glycol (400) in pure water and stir for 2h;

[0092] S2. The mixed solution obtained in step S1 was dried in a vacuum drying oven at 120°C to obtain a black solid after drying for 48 hours;

[0093] S3. The solid obtained in step S3 was ground and heated from 25°C to 500°C under an inert atmosphere at a heating rate of 5°C / min for 3 hours, and then naturally cooled to room temperature to obtain a phytic acid-Ti3C2 MXene composite material.

[0094] This comparative example also provides a method for preparing an electrode sheet: the phytic acid-Ti3C2 Mxene composite material obtained above is mixed with acetylene black and a binder PVDF in a mass ratio of 7.0:1.5:1.5, and N-methylpyrrolidone is added for stirring to form a uniform slurry, which is coated on a copper foil and dried in a vacuum drying oven for 12 hours to obtain an electrode sheet.

[0095] Performance Testing

[0096] The phytic acid-Ti3C2 MXene composite material and the Ti3C2 MXene material prepared by the present invention were subjected to XRD, SEM and TEM detection and analysis, and the results obtained are as follows: Figure 1-3shown.

[0097] Battery assembly: The battery assembly was carried out in a glove box filled with argon gas, using the negative electrode sheet obtained in the embodiment and the comparative example as the working electrode, the metal potassium sheet as the counter electrode, the diaphragm as glass fiber, and the electrolyte as KPF6 to assemble button cells for electrochemical performance testing.

[0098] Charge and discharge test: The voltage range of button cell charge and discharge is 0.1~3V, and the current is 100~1000mAg within this voltage range. -1 The current density was used for charge and discharge cycle test. The test results are shown in Table 1 and Figures 4 to 6 shown.

[0099] Figure 1 The XRD patterns of Example 1 and Comparative Example 1 show that the diffraction peaks of the phytic acid-Ti3C2MXene composite material are basically consistent with those of the Ti3C2 MXene material, indicating that phytic acid does not change the physical structure of the layered Ti3C2 MXene material. At the same time, a larger steamed bun peak appears at around 27°, indicating that the uncrystallized component in the material increases, indicating the presence of more disordered structures, such as disordered carbon.

[0100] Figure 2 a and Figure 2 b are SEM images of Ti3C2 Mxene material and phytic acid-Ti3C2Mxene composite material of Example 1 of the present invention, respectively. By comparison, it can be found that the phytic acid-Ti3C2Mxene composite material prepared by the present invention is still a layered structure, and phytic acid forms an obvious coating layer on the surface of Ti3C2 Mxene, so that when the composite material of the present invention is used for the negative electrode material of potassium ion battery, the structural stability of the phytic acid-Ti3C2Mxene composite material can be improved, and the volume expansion of Ti3C2 Mxene can be inhibited, thereby effectively improving the cycle performance of the potassium ion battery.

[0101] Figure 3 a and Figure 3 b correspond to the TEM images of Ti3C2 Mxene material and the phytic acid-Ti3C2Mxene composite material of Example 1 of the present invention. By comparison, it can be found that the interlayer spacing of the phytic acid-Ti3C2Mxene composite material prepared by the present invention is increased compared with Ti3C2Mxene.

[0102] Figure 4 The phytic acid-Ti3C2 MXene composite material of Example 1 of the present invention and the Ti3C2MXene material of Comparative Example 1 were used to make button batteries at 100 / Ag -1 The charge and discharge cycle performance diagram under current density. Figure 4It can be seen that the first discharge specific capacity of the phytic acid-Ti3C2 Mxene composite material prepared in Example 1 is 742.2 / Ahg -1 After 100 cycles, the specific capacity is 185.5 / Ahg -1 The first discharge capacity of Ti3C2 MXene material is 248.3 / Ahg -1 After 100 cycles, the specific capacity is only 90 / Ahg -1 From the above results, it can be seen that the use of phytic acid composite Ti3C2 MXene can effectively improve the reversible capacity and cycle stability of the material.

[0103] Figure 5 The phytic acid-Ti3C2 Mxene composite material of Example 1 of the present invention is made into a button battery at 1000 / Ag -1 The charge and discharge cycle performance diagram under current density. Figure 5 It can be seen that the phytic acid-Ti3C2 Mxene composite material prepared in Example 1 has an initial discharge capacity of 543.1 / Agh -1 After 500 cycles, the specific capacity remains at 128.8 / Ahg -1 It can be seen that the phytic acid-Ti3C2 Mxene composite material prepared by the present invention still has good long cycle stability and structural stability under high-power charge and discharge conditions.

[0104] Figure 5 The phytic acid-Ti3C2 MXene composite material of Example 1 of the present invention and the Ti3C2MXene material of Comparative Example 1 are used to make button batteries at 100-1000 / Ag. -1 The charge and discharge rate performance diagram under current density. Figure 5 It can be seen that the phytic acid-Ti3C2 Mxene composite material prepared in Example 1 has a high molecular weight at 100, 200, 300, 500, 1000 / Ag -1 The reversible capacities obtained at current densities are 144.8, 92.3, 57.4, 52.3 and 43.3 / Ahg -1 However, the capacity of Ti3C2 MXene material at the same rate current density is 50.0, 45.0, 38.0, 30.0 and 22.0 / Ahg -1 From the above results, it can be seen that the phytic acid-Ti3C2Mxene composite material prepared in the present invention can effectively improve the specific capacity and rate performance of the material at a high current density.

[0105] The electrode sheets obtained in the embodiments of the present invention and the comparative examples were made into button batteries and the current density was 100 / Ahg -1 The charge and discharge cycle test was carried out under the following conditions, and the results are shown in Table 1.

[0106] Table 1

[0107]

[0108]

[0109] It can be seen from Table 1 that the first discharge specific capacity of the phytic acid-Ti3C2 Mxene composite material prepared by the present invention reaches 717.2 / Ahg -1 Above, the discharge capacity can reach 125.3 / Ahg after 500 cycles. -1 Above, the first coulombic efficiency (first charge specific capacity / first discharge specific capacity) reaches more than 57.8%. It can be seen from Example 1 and Comparative Example 1 that the phytic acid-Ti3C2 Mxene composite material prepared by the present invention is significantly improved in cycle stability and specific capacity compared with the Ti3C2 Mxene material. It can be seen from Example 1 and Comparative Example 2 that the content of phytic acid can affect the material capacity and cycle stability. Too little phytic acid content will make it difficult to form a coating layer on the surface of Ti3C2 Mxene, causing the material to easily expand in volume during the charge and discharge cycle, and reducing the active sites of the material, thereby reducing the cycle stability and capacity of the material. It can be seen from Example 1 and Comparative Example 3 that the present invention uses liquid nitrogen extreme freezing to effectively keep the structure of the phytic acid intercalated in the Ti3C2 Mxene material unchanged, avoiding the collapse of the material structure, which is conducive to improving the capacity and cycle stability of the material.

[0110] The above embodiments are preferred experimental methods of the present invention, but the implementation methods of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a phytic acid-Ti3C2 MXene composite material, characterized in that: The following steps are involved: S1. Ti3C2 Mxene, phytic acid and a solvent are placed in a solvent and stirred to obtain a mixed solution; S2. freezing the mixed solution obtained in step S1 with liquid nitrogen to obtain a solid product; S3. freeze-drying the solid product obtained in step S2 under vacuum conditions to obtain an aerogel; S4. The aerogel obtained in step S3 is heat-treated under an inert atmosphere and then cooled to obtain a phytic acid-Ti3C2MXene composite material; In the step S1, the mass ratio of Ti3C2 Mxene to phytic acid is 1:1.5-5.

2. The preparation method according to claim 1, characterized in that: In the step S1, the mass ratio of Ti3C2Mxene to phytic acid is 1:1.5-2.

5.

3. The preparation method according to claim 1, characterized in that: The heat treatment in step S4 is to heat the material from ambient temperature to 500-600° C. at a heating rate of 1-10° C. / min and then keep the temperature.

4. The preparation method according to claim 3, characterized in that: The insulation time is 1 to 3 hours.

5. The preparation method according to claim 1, characterized in that: The dissolution promoter in step S1 is one or more of polyethylene glycol, N,N-dimethylformamide, and dimethyl sulfoxide.

6. The preparation method according to claim 1, characterized in that: In the step S1, the mass ratio of the dissolution agent to the phytic acid is 1:60-200.

7. A phytic acid-Ti3C2 MXene composite material prepared according to any one of claims 1 to 6.

8. An electrode, characterized in that: The electrode comprises the phytic acid-Ti3C2MXene composite material as described in claim 7.

9. The electrode according to claim 8, characterized in that The weight percentage of the phytic acid-Ti3C2 MXene composite material in the electrode is 65-75%.

10. A potassium ion battery, characterized in that: The potassium ion battery comprises the electrode according to claim 8 or 9.

Citation Information

Patent Citations

  • MXene / metal phosphide composite material, and anode material and preparation and application thereof

    CN111180695A

  • Method for preparing nitrogen-phosphorus co-doped MXene negative electrode material and application of nitrogen-phosphorus co-doped MXene negative electrode material

    CN115911363A

  • Mxene / metal composite aerogel, preparation method therefor and use thereof, and thermal interface material containing same

    WO2021056851A1